First multi-reactive dextran-based inisurf for atom transfer radical polymerization in miniemulsion. (5th October 2015) - Wu, Man; Forero Ramirez, Laura M.; Rodriguez Lozano, Ana; Quémener, Damien; Babin, Jérôme; Durand, Alain.; Marie, Emmanuelle; Six, Jean-Luc; Nouvel, Cécile
Highlights: Dextran-based inisurfs (acting both as initiator and stabilizer) are synthesized Surface active properties of inisurfs similar to amphiphilic dextran derivatives Miniemulsion AGET–ATRP of BA is optimized with model initiator and inisiurf ATRP groups are in contact with oil/monomer interface and initiate polymerization Kinetics and nanoparticle characteristics are correlated to experimental conditions Abstract: A multi-reactive polysaccharide-based inisurf (acting both as initiator and stabilizer) has been designed for the first time from dextran with the aim of preparing dextran-covered nanoparticles with covalent linkage between core and coverage. This inisurf was used for polymerizing butyl acrylate in miniemulsion by AGET–ATRP. Both hydrophobic phenoxy groups and initiator groups (bromoisobutyryl ester) were introduced within hydrophilic dextran chain, conferring it amphiphilic and macroinitiator characters. Amphiphilic properties of dextran inisurfs have been evidenced as well as their ability to stabilize the direct miniemulsion of n -butyl acrylate. After optimization of polymerization conditions with model studies, assays were successfully realized with dextran-based inisurfs. Because of their amphiphilic character, inisurfs migrated at oil/water interface and initiated polymerization from bromoisobutyryl ester groups. Therefore graft copolymers were produced at oil/water interface, due to the multifunctional character of these inisurfs and constituted the particle inner core with covalent links to the dextran coverage.